Pengaruh Growth Asset Dan Intrinsic Value Terhadap Harga Saham Pada Perusahaan Food And Beverage Di bursa efek indonesia - Indah Lia Puspita (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2013)
Asset growth is the annual change of total assets a re expected to be received by an entity as a result of past transactions. High asset growth i s assumed to be attractive for the investor confide nce that would result in a company's stock price change s. Intrinsic value of shares is the value that is often used to assess whether a stock is undervalued or ov ervalued position. PBV ratio gives another indication of how investors view a company and how this ratio information can be used for investors in making investment decisions. With a high PBV ra tio is expected to return the company's stock is also high. The purpose of this study was to test the asset gro wth variable and the intrinsic value of stock prices. The sample used in the writing of this thesis consi sts of 16 companies engaged in food and beverage industry. The analysis used the multiple linear re gression analysis with least squares equations and hypothesis testing using the t-statistic for testin g the partial regression coefficients. It also con ducted a test that includes the assumption of classical test for normality, multicollinearity test, test heteroskedastisitas and test autocorrelation. Proce ssing data is done by using the help of the statist ical product and service solutions (SPSS) version 16. The results of testing the hypothesis test-T or obt ained partially value of T for asset growth was 0,035 and value of T for the intrinsic value was 0,044. B ased on the above T-test results can be concluded that the probability value ˂ 0,05 then there is sufficient evidence to reject Ho and accept Ha. Keywords: Asset Growth, Intrinsic value ,Stocks, and Stock P rice